Acellular Dermal Allograft for Sellar Repair after Transsphenoidal Approach to Pituitary Adenomas - Gaynor, Brandon G.; Benveniste, Ronald J.; Lieberman, Seth; Casiano, Roy; Morcos, Jacques J. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives Our practice has transitioned from using fat autograft to acellular dermal matrix (AlloDerm, LifeCell Corp, Woodlands, Texas, USA). We present the largest series to our knowledge of AlloDerm for sellar floor repair after transsphenoidal approach to pituitary adenoma and compare rates of postoperative cerebrospinal fluid (CSF) leak with an earlier cohort of patients whose CSF leaks were repaired with fat autograft.Design This is a retrospective cohort study comparing sellar repair with fat autograft versus inlay Alloderm between the years 2003 and 2012. The primary end point was postoperative CSF leak.Results A total of 429 patients (368 primary; 83 revision operations) without intraoperative lumbar drainage were included. A total of 18 postoperative CSF leaks were observed (3.9%). Intraoperative CSF leak occurred in 160 cases (35.5%). Among this subset of patients with intraoperative CSF leak, 95 underwent repair with AlloDerm and 46 underwent repair with fat autograft, with postoperative CSF leak rates of 8.4% and 15.2%, respectively (p = 0.34, chi-square test); 19 patients underwent repair with other techniques or no repair at all, with postoperative leak rate of 0%.Conclusions AlloDerm is an effective alternative to fat autograft in cases of low-flow CSF leak following transsphenoidal resection of pituitary adenoma.
Keywords: pituitary adenoma; acellular dermal matrix; AlloDerm; fat autograft; cerebrospinal fluid leak; transsphenoidal surgery